Prevalence of Side Effects of Propofol Anesthesia among Adult and Pediatric Patients Undergoing Surgery - Khaled D Alsaeiti; Fathi M Elbraky; Salem A Ibkhatra; Khawla A Al-Zoubi; Ghada A Alagoury; Fatima F Al-Farajani; Hawa Al-Kharaz; Fatima A Al-Megrahi (Apollo Medicine)
Introduction: Propofol is a short-acting medication that lowers awareness and causes a transient memory loss. It is given intravenously. The aim of this study was to assess the prevalence of various side effects of the use of propofol as an anesthetic in various surgical procedures and to compare their prevalence among adults and children. Materials and Methods: One hundred patients were included in the study, fifty adults and fifty of children, who underwent various types of surgery and received propofol anesthesia, at Pediatrics Hospital, Benghazi Medical Center (BMC) and Al-Hawari hospital, from September to November 2019. Results: The mean age was 6.37 Â± 4.18 years in the pediatric group (ranging from 1 to 15 years) and 40.0 Â± 17.03 years in the adult group (range from 16 to 97 years). The indication of surgery among the adult group was cholecystectomy (14 patients, 28%), followed by ENT operations (12 patients, 24%), while the indication of surgery among the pediatric group was tonsillectomy (20 patients, 40%), followed by hernia repair (15 patients, 30%). Thirty-five adults (70%) and 40 children (80%) suffered different types of complications during the study. Pain at the site of propofol injection was the most common complication. It was observed in 21 adult patients (42%) and 23 children (46%). Bronchospasm developed among 11 children who underwent tonsillectomy. Low blood pressure was more prevalent among adult patients (14 patients, 28%). An arrhythmia was developed in nine patients (six adults and three children). Two adults and five children experienced delayed recovery from anesthesia. The recovery time was 14.67 Â± 8.37 min (5â€"45 min), Conclusion: Burning at site of propofol injection is the most common side effect of propofol anesthesia; other complications need further evaluation by more detailed studies.